Evaluation of the Cytotoxicity of Two Types of Triple Antibiotic Paste on Human Permanent Dental Apical Papilla Stem Cells: an in vitro Study - Rezvan Rafatjou; Arghavan Kamali Sabeti; Bahar Ahmadi; Sara Soleimani Asl; Maryam Farhadian (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The use of a new antimicrobial combination in the regenerative endodontic treatment of immature teeth pulp necrosis is a well-known method. Concerns have been raised about the destructive effect of this combination on the stem cells from the apical papilla of permanent human teeth, and there is a study gap. Purpose: The main objective of the present study was to investigate the cytotoxic effect of modified triple antibiotic paste (mTAP) on stem cells from the apical papilla (SCAPs) of permanent human teeth. Materials and Method: In this in vitro study, stem cells were removed from the immature teeth. After cultivation and third passage, metronidazole, ciprofloxacin, minocycline, and clindamycin were placed in the cell culture medium alone , paired, and in combinations as triple antibiotic paste (TAP) (metronidazole, ciprofloxacin, and minocycline) and mTAP (metronidazole, ciprofloxacin, clindamycin) with doses of 25, 50, 100, 200, 400μg/ml. After 1 and 3 days, cell viability in the culture medium was assessed using the MTT method ([4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide). SPSS software version 24, descriptive statistics methods, and statistical tests such as Kruskal-Wallis and Mann-Whitney tests were adopted to analyze the data. Results: Analysis of MTT findings indicated that the use of mTAP at 100μg/ml and TAP at 200μg/ml had no adverse cytotoxic effect on stem cells in the first 24 hours, compared to the control group. The cell viability decreased at higher concentrations, although it was not statistically significant. After 72 hours, the toxicity of concentrations higher than 100μg/ml of mTAP and 400 μg/ml of TAP significantly mitigated the percentage of viable cells. Conclusion: The obtained results demonstrated that the concentration of 100 μg/ml of mTAP could replace TAP in regenerative endodontic treatments at the studied time intervals without worrying about the toxicity.